Transcutaneous neuromuscular electrical stimulation can improve swallowing function in patients with dysphagia caused by non‐stroke diseases: a meta‐analysis. (23rd April 2013) - Tan, C.; Liu, Y.; Li, W.; Liu, J.; Chen, L.
Summary: There is still debate over whether the effect of transcutaneous neuromuscular electrical stimulation (NMES) in dysphagia rehabilitation is superior to traditional therapy (TT). The purpose of this meta‐analysis was to assess the overall efficacy by comparing the two treatment protocols. Published medical studies in the English language were obtained by comprehensive searches of the Medline, Cochrane and EMBASE databases from January 1966 to December 2011. Studies that compared the efficacy of treatment and clinical outcomes of NMES versus TT in dysphagia rehabilitation were assessed. Two reviewers independently performed data extraction. Data assessing swallowing function improvement were extracted as scores on the Swallowing Function Scale as the change from baseline (change scores). Seven studies were eligible for inclusion, including 291 patients, 175 of whom received NMES and 116 of whom received TT. Of the seven studies, there were two randomised controlled trials, one multicentre randomised controlled trial and four clinical controlled trials. The change scores on the Swallowing Function Scale of patients with dysphagia treated with NMES were significantly higher compared with patients treated with TT [standardised mean difference (SMD) = 0·77, 95% confidence interval (CI): 0·13 to 1·41, P = 0·02]. However, subgroup analysis according to aetiology showed that there were no differences between NMES and TT in dysphagia post‐stroke (SMD = 0·78, 95% CI: −0·22 to 1·78, P = 0·13, 4 studies, 175 patients). No studies reported complications of NMES. NMES is more effective for treatment of adult dysphagia patients of variable aetiologies than TT. However, in patients with dysphagia post‐stroke, the effectiveness was comparable.